Serial offenders: conceptual analysis and profile of criminals operating in Belo Horizonte - Faria, Antonio Hot Pereira de (2019)
This paper seeks two main objectives. First, it carries out a conceptual approach to the genre of serial criminals. Secondly, it presents empirical results on the performance of serial criminals in Belo Horizonte / MG between 2011 to 2013. The methodology starts with a theoretical review on the issue of serial criminals and other related concepts. The second step consisted of collecting and analyzing data on police occurrences. Results indicate that the serial criminals have a profile characterized by the predominance of brown young men (18 to 25 years old), originating in the capital city of Minas Gerais, with low educational level, holding lower occupational status. The events perpetrated show that there is no specificity in the activities of offenders, fact that removes the professionalism hypothesis, suggesting that their behavior conform with the notions of chronic / habitual offenders found in the literature.